EFFECT OF TEMPERATURE ON CORROSION OF CARBON STEEL BOILER TUBES IN DILUTE SODUIM CHLORIDE SOLUTION - Rassoul, G.A.; Rzaige, D.R. (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The corrosion behavior of carbon steel at different Temperatures and in water containing different sodium chlorideconcentrations under 3 bar pressure has been investigated using weight loss method . The carbon steel specimens wereimmersed in water containing (100,400,700,1000PPM) of NaCl solution and under temperature was increased from(90-120ºC) under pressures of 3 bar. The results of this investigation indicated that corrosion rate increased with NaClconcentrations and Temperature.